Erythropoietin in Spinocerebellar Ataxia Type 2: Feasibility and Proof‐of‐Principle Issues from a Randomized Controlled Study. Issue 7 (23rd May 2022) - Rodriguez‐Labrada, Roberto; Ortega‐Sanchez, Ricardo; Hernández Casaña, Patricia; Santos Morales, Orestes; Padrón‐Estupiñan, Maria del Carmen; Batista‐Nuñez, Maricela; Jiménez Rodríguez, Daise; Canales‐Ochoa, Nalia; Peña Acosta, Arnoy; Medrano Montero, Jacqueline; Labrada Aguilera, Pedro Enrique; Estupiñán Rodriguez, Annelie; et al.
Abstract: Background: Several pieces of evidence have shown the neurotrophic effect of erythropoietin (EPO) and its introduction in the therapeutic practice of neurological diseases. However, its usefulness in the treatment of spinocerebellar ataxia type 2 (SCA2) has not been proven despite the fact that it is endogenously reduced in these patients. Objective: The study aims to investigate the safety, tolerability, and clinical effects of a nasally administered recombinant EPO in SCA2 patients. Methods: Thirty‐four patients were enrolled in this double‐blind, randomized, placebo‐controlled, phase I–II clinical trial of the nasally administered human‐recombinant EPO (NeuroEPO) for 6 months. The primary outcome was the change in the spinocerebellar ataxia functional index (SCAFI), while other motor, neuropsychological, and oculomotor measures were assessed. Results: The 6‐month changes in SCAFI score were slightly higher in the patients allocated to NeuroEPO treatment than placebo in spite of the important placebo effect observed for this parameter. However, saccade latency was significantly decreased in the NeuroEPO group but not in placebo. The frequency and severity of adverse events were similar between both groups, without evidences of hematopoietic activity of the drug. Conclusions: This study demonstrated the safety and tolerability of NeuroEPO in SCA2 patients after 6 months of treatments and suggested a small clinical effect of this drug on motor and cognitive abnormalities, but confirmatory studies are warranted. © 2022 International Parkinson and Movement Disorder Society.